Diseño de una Planta de Tratamiento de Aguas Residuales en la microempresa de lácteos Digna Isabel - Chico Chafla, María de los Ángeles (2023)
This research based on designing a wastewater treatment plant for the dairy microenterprise “Digna Isabel”. The effluent analyzed in the UNACH laboratories, determining the physicochemical and microbiological parameters subject to comparison with the regulations set forth in the TULSMA. Proposing a treatment that will help minimize oil and grease contaminants with a value of 1673 mg/L, DBO5 of 873.1 mgO2/L, DQO of 1647mg/L, dissolved salts 64.7 mg/L, settleable solids (SS) of 14 mg/L, total suspended solids (SST) of 670 mg/L and total solids (ST) of 1814 mg/L, parameters that did not meet the maximum limit permissible, establishing the following phases and equipment that will constitute the treatment plant. The appropriate treatment system established, starting from a homogenizing tank, a grease trap where the outgoing effluent will receive its dose of coagulant and flocculant estimated by the laboratory, then said effluent will pass to the high-rate decanter that generates the residual sludge that will be sent. to the beds, finally It pass through the activated sludge system that consists of an aeration tank and a secondary decanter that will reduce the concentration of the remaining pollutants. Finally, through a theoretical balance of contaminant removal, the efficiencies for each equipment were established, such as: In the grease trap removals of 95% of oils and greases, 5% of DBO5 and 3% of DQO. Coagulation and flocculation an elimination of 75.79% of DQO, 86.21% of SST, 98.8% of oils and fats and 80% of dissolved salts. High-rate decanter with a removal of 93% ST, 40% DBO5, 90% SS, 30% DQO and 50% oils and fats. Finally, the activated sludge system removes 80% of DBO5, 13% of DQO, 35% of oils and fats, 30% of SS and 25% of dissolved salts.